KOORDINASI PENYIDIK KEPOLISIAN DAN JAKSA PENUNTUT UMUM DALAM SISTEM PERADILAN PIDANA (CRIMINAL JUSTICE SYSTEM) DI INDONESIA - Syarifudin, Syarifudin; Zulaidi, Zulaidi (Majalah Keadilan, 2020)
ABSTRACK Positive cooperative relationships in accordance with their respective functions and authorities between Police investigators and the Public Prosecutors in order to handle cases in preparation for prosecution will determine the outcomes to be decided by the panel of judges in the Court. In this research type of approach that will be used is the type of statute approach (statute approach) is the approach done by reviewing all laws and regulations related to cooperation in performing the duties and authority of Investigation and Prosecution. Coordination of investigators and public prosecutors in the criminal justice system in Indonesia shall be conducted in the event of notifying the investigation of the prosecutor by the investigator, the notice of suspension of investigation by the investigator to the prosecutor, the submission of the case file by the investigator to the prosecutor in the context of pre prosecution and the prosecutor, the request for the extension of the period of detention by the investigator to the public prosecutor, the grant of a letter of delegation of the case and the indictment by the public prosecutor to the investigator and authorized by the public prosecutor to delegate the case file by presenting the defendant, witness, in quick event checks. Keywords: Investigator and Investigation; Public Prosecutor and Prosecution